Caregivers’ Performance towards Pressure Ulcer Preventive Measures for Spinal Cord Injury Patients - Ahmed Thamer Saud; Alaa Jawad Kadhim (Kufa Journal for Nursing Sciences)
Objectives: The present study aimed to evaluate caregivers’ performance concerning pressure ulcer preventive measures for spinal cord injury patients.